Loop input: fostering creativity among teachers - Ahmad Jefiruddin, Farah Diyana; Abd Rahman, Nur Fatin Nabila; Aralas, Dalia; Ismail, Lilliati; Othman, Moomala (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
The present paper aims to analyze the role, potential and advantage of loop input approach within the context of teachers’ creativity and professional development. Loop input approach allows for experiential learning where teachers replicate a lesson that will later be put to practice in their actual classroom and experience it themselves for them to be able to reflect on their own practices. Research findings suggest that at the reflective stage of loop input approach, teachers often recognize and point out the issues in their own teachings such as time management, learning style and content of learning. This process of reflection fosters metacognition and allows teachers to develop new knowledge and ideas as how to approach their teachings more effectively with the learners in mind. The employment of loop input perfectly captures teachers’ teachings in the clearest way possible. This approach plays with cognitive skills which help with teachers’ creativity and professional growth. In fact, experimenting and having a clear idea of what the teacher expects from the learners is very important in producing a conducive teaching environment. It is anticipated that the loop input, if implemented within Malaysian teacher training context, will catalyst teachers’ creativity as well as professional growth through its capacity to provide experiential learning and reflection on skills and competence.